THE ROLE AND SIGNIFICANCE OF THE CHANG INSTRUMENT IN UZBEK FOLK MUSIC PERFORMANCE - Xujaeva Sabina Akmal qizi (Journals Park Publishing, 2025)
This article discusses the role and importance of the chang instrument in the system of Uzbek folk music performance, its expressive capabilities, and its contribution to the preservation and development of national musical heritage. The study analyzes the chang’s function within ensembles, its unique timbre, and distinctive performance techniques.
Keywords: Chang instrument, folk instruments, performance, national music, ensemble, style, cultural heritage.